2022
DOI: 10.1111/jgh.16039
|View full text |Cite
|
Sign up to set email alerts
|

Liver abnormalities in celiac disease and response to gluten free diet: A systematic review and meta‐analysis

Abstract: Background and Aim Liver involvement in celiac disease (CeD) is known but its various etiologies and the effect of gluten free diet (GFD) on it is understudied. Methods We searched PubMed, Medline and Embase databases from date of inception to March 7, 2022, to look for studies reporting on CeD and liver abnormalities. Pooled proportion of CeD patients with deranged transaminases, etiologies of various other liver diseases with CeD and the response to GFD were estimated. Subgroup analyses based on the age grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
(74 reference statements)
0
2
0
1
Order By: Relevance
“…Other large meta-analyses have shown that 86.39% of patients with confirmed celiac disease and liver manifestations (95% CI: 80.04-90.95, I2 = 74%) responded with improvement to a gluten-free diet [14]. ALT and albumin levels have improved 6 and 12 months after gluten-free diet initiation as well [15].…”
Section: Discussionmentioning
confidence: 96%
“…Other large meta-analyses have shown that 86.39% of patients with confirmed celiac disease and liver manifestations (95% CI: 80.04-90.95, I2 = 74%) responded with improvement to a gluten-free diet [14]. ALT and albumin levels have improved 6 and 12 months after gluten-free diet initiation as well [15].…”
Section: Discussionmentioning
confidence: 96%
“…Low high density lipoprotein (HDL) has consistently been associated with untreated CD [40], and the combination of unexplained iron-de ciency anemia and low HDL may be particularly suggestive of CD [41]. Longitudinal studies have found that these lab abnormalities typically resolve after initiation of a GFD, including anemia [42], transaminitis [43], and low HDL [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Формирование ГТ может быть результатом включения аутоиммунных процессов, приводящих к повреждению паренхимы печени анти-ТТГ, что подтверждается нормализацией уровней АЛТ и АСТ на фоне строгого соблюдения безглютеновой диеты [9,16,19]. Кроме того, повреждение печени при целиакии может быть обусловлено выработкой антител к гепатоцитам у лиц, имеющих генетическую предрасположенность к формированию аутоиммунных заболеваний.…”
Section: обсуждение результатовunclassified